Diagnóstico radiográfico e tomográfico de osteocondrose dissecante em tarso de cão - Ferreira, Márcio Poletto; Nóbrega, Fernanda Vieira; Ferrigno, Cássio Ricardo Auada; Alievi, Marcelo Meller; Zang, Luciana; Brose, Mariana de Mattos; de Souza, Mariana de Jesus; Bing, Rafaela Scheer (Acta Scientiae Veterinariae, 2017)
Background: The tarsal joint is the third most commonly joint affected by osteochondrosis in dogs. This joint is affected in 4 to 9% of the cases, and in 50% of these cases the disease is bilateral. Radiological signs include defect in the subchondral bone, sclerotic margin, and fragment of mineralized cartilage. Dorsoplantar in flexion and oblique radiologic images are necessary to show tarsal osteochondrosis. Computed tomography avoid overlap of bone structures and allows better visualization of subchondral lesions, showing the exact location, size and number of fragments. The objective of this study is to report a case of bilateral osteochondrosis dissecans in tarsal joint in Rottweiler. Case: A female Rottweiler was examined and presented a history of pain and difficulty in raising the pelvic limbs. There was pain in the right tibiotarsal joint (RTJ) with evident joint cracking and, after three months, the left pelvic limb started to show the same signs. Radiographic examination of the RTJ showed a small osteochondral fragment in the distal medial border of the medial malleolus of the tibia, subchondral sclerosis with radiolucent area in the medial malleolus of the tibia, and a small lateral periarticular osteophyte in the intertarsal joint. The left tibiotarsal joint (LTJ) showed mild articular incongruity and minor increase in radiological interlinear space, diffuse sclerosis in the medial malleolus and in the subchondral surface of the trochlear crest. This exam also showed a small radiolucent area in the medial malleolus of the tibia, a small fragment of radiopaque adjacent bone, and minor subchondral bone irregularity in the medial margin of the medial trochlea. The radiographic examination of the RTJ was inconclusive. Computed tomography was requested and suggested the diagnosis of medial osteochondritis dissecans in the distal talus. The most important tomographic signs were irregularity of the subchondral bone in the caudal region of the distal talus associated to isolated bone fragment, irregularity of the distal and caudal portion of the medial malleolus of the tibia associated with the presence of free adjacent osteophyte. Discussion: Only 4 to 9% of the dogs that develop osteochondrosis present this lesion in the tarsus. The Rottweiler is the breed most affected by this disease, such as the subject of this case report, and is also the breed most frequently affected in the lateral region of the tarsus. It is a fast-growing large breed, a common characteristic in animals affected by osteochondrosis. Bilateral cases are most common in young dogs, such as the patient of this case report. Clinical manifestation of pain and lameness is frequent in this type of disease, and lameness can occur in only one of the affected limbs. The dog of this study presented lesion in the medial region of the trochlea of the talus, one of the regions that present high incidence of osteochondrosis. Radiographic examination was efficient to suggest lesions in the medial region of the talus. However, only 10% of the dogs with osteochondrosis of the tarsus are diagnosed by this technique. The definitive diagnosis was not provided by radiographic examinations in this patient. Computed tomography has several advantages over conventional radiography, such as eliminating overlap of structures, decreasing image complexity, and increasing the ability to identify specific structures. This examination allowed us to reach the diagnosis of osteochondrosis dissecans in the right talus of this dog. A scan was not performed on the contralateral limb (LTJ), because the lesions observed on radiographic examination were similar to the lesions observed in the right pelvic limb.